Division in Vedic Mathematics - Parajuli, Krishna Kanta (Journal of Nepal Mathematical Society, 2025)
Vedic Mathematics, derived from ancient Hindu scriptures known as the Vedas, offers a unique and efficient approach to arithmetic, algebraic and trigonometric calculations. Among its 16 foundational sutras and 13 sub-sutras, division is addressed with remarkable simplicity and speed. Out of them “Nikhilam”, “Urdhva Tiryagbhyam (Dhwajanka)” and “Paravartya” Sutras are particularly effective in performing division operations. These methods transform complex problems of division into manageable mental calculations, often eliminating the need for traditional long division techniques. The Vedic approach not only enhances computational speed but also promotes mental flexibility and problem-solving skills. Through some practical applications, this article demonstrates how Vedic Mathematics can simplify division, offering an alternative method that is valuable for complex computations. Its integration into modern education could revolutionize teaching methodologies, making mathematics more accessible and enjoyable for students.